1993
DOI: 10.1364/ao.32.004685
|View full text |Cite
|
Sign up to set email alerts
|

Submicrometer displacement sensing using inner-product multimode fiber speckle fields

Abstract: A multimode fiber sensor using the intensity inner product of speckle fields is presented. The sensitivity and the dynamic range of the displacement sensing are quantitatively analyzed. We show that the sensitivity of displacement can be in the submicrometer range. Experimental performances show that the results are consistent with the calculated results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 8 publications
0
44
0
6
Order By: Relevance
“…Therefore, fiber specklegrams can be used for sensing purposes. Since the 1980s, numerous designs and arrangements of sensors based on fiber specklegram have been proposed to measure vibration, displacement, strain, and acoustic waves [3][4][5][6]. These first sensors using bulky assemblies and signal processing was very extensive and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fiber specklegrams can be used for sensing purposes. Since the 1980s, numerous designs and arrangements of sensors based on fiber specklegram have been proposed to measure vibration, displacement, strain, and acoustic waves [3][4][5][6]. These first sensors using bulky assemblies and signal processing was very extensive and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…These particular characteristics of the speckle phenomenon obtained in multimode fibers are used in sensing technology. In recent years several studies have been reported in vibration sensing [1], displacement [2], distance [3], cracks in concrete structures [4], and blood flow [5]. In all these cases, they have used multimode optical fibers with core diameters from 50 to 100 μm and, usually, silica fibers.…”
Section: Introductionmentioning
confidence: 99%
“…These sensors have been widely studied by their potential applications in several engineering fields. [2][3][4][5][6][7][8][9][10][11][12]. Holographic FSS setups have been mainly developed by recording speckle patterns on photorefractive materials and optically performing self-correlation operations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%